Determinants of sports result in kayaking on the example of junior athletes - Rynkiewicz, M.; Rynkiewicz, T.; Zurek, P. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
The aim of this study was to identify the determinants of sports results in kayaking. We conducted the complex examination of condition and coordination motor skills of kayakers, and determined their relationship to the results of specialist tests. Moreover, we tried to define the level of motor skills which is typical for Polish junior kayakers and compare our findings to the results reported by other authors. The study included 18 kayakers at mean age of 16.2 years. The following tests were conducted: 2000 m and 1000 m paddling in a kayak, maximum power test during kayak ergometer paddling, VO2 max and power developed during kayak ergometer paddling at intensity corresponding to ventilator threshold (VT), body composition, 1500 m track running, measurements of strength endurance and power developed during series of six repetitions bench press and bench pull. Also the levels of dynamic and static balance were determined. Statistically significant relationship was documented between paddling speed and power developed at a threshold intensity (VT), the velocity of barbell movement during bench press and bench pull, and the level of static balance. Moreover, a strong correlation was observed between maximum power during kayak ergometer paddling and the kayak paddling speed. According to these findings, kayakers should show high level of power at VT intensity and maximum power determined during kayak ergometer paddling. Moreover, they should be characterized by high velocity of barbell movement during bench press and bench pull, and high level of static balance. The results of this study enabled us to determine the typical level of preparation of Polish junior kayakers. Body structure and capacity of examined kayakers did not differ markedly from relevant values reported by other authors.